Efecto de la temperatura de colada sobre la resistencia al desgaste, dureza y fluidez mediante modelo en espiral de las aleaciones za: zn-22%al y zn-27%al fundidas y colada en molde de arena en seco - Rojas Diaz ., Edward Ossmar Olaff (2019)
The effect of the casting temperature on the wear resistance, hardness and flowability by spiral mold in the ZA alloys: Zn - 22% Al (ZA-22) and Zn - 27% Al (ZA-27) cast was studied and cast in sand mold. For which the casting temperatures of 500, 540, 580, 620 and 660 ° C were considered, it was experimented with specimens according to ASTM G77 standard for the wear test, specimens according to ASTM E-140 standard for the hardness test and specimens in spiral form according to the Chneider method to assess fluency. The experimental results show that when increasing the casting temperature from 500 to 660 ° C, the hardness (HB) and wear resistance (mg) decrease for both types of alloy. Obtaining the best values of hardness and resistance to wear in the zinc alloy - 22% aluminum for being eutectoid. Regarding the fluidity, the increase of the temperature of casting from 500 to 660 ° C, the fluidity (cm) increases in both types of alloy, because when increasing the temperature of casting increases the overheating delaying the nucleation and growth of solid grains. And the best flow values were obtained for the zinc - 22% aluminum alloy. It also shows that at low casting temperatures the best values of hardness and wear resistance are obtained for both alloys under study, because they consist of fine grains. It is concluded that the casting temperature significantly affects the properties evaluated in the zinc alloy - 22% aluminum and zinc - 27% aluminum, according to the statistical analysis with a confidence level of 95%.